Responses to Treatment With Teriparatide in Patients With Atypical Femur Fractures Previously Treated With Bisphosphonates. (7th February 2017) - Watts, Nelson B; Aggers, Deborah; McCarthy, Edward F; Savage, Tina; Martinez, Stephanie; Patterson, Rachel; Carrithers, Erin; Miller, Paul D
ABSTRACT: If oversuppression of bone turnover explained the association between bisphosphonate use and atypical subtrochanteric femur fractures (AFF), this could be reversed with anabolic treatment such as teriparatide. We conducted a prospective, open‐label study in patients previously treated with bisphosphonates who sustained AFF, examining the response to 24‐month treatment with teriparatide on bone mineral density (BMD), trabecular bone score (TBS), bone turnover markers (BTM), and fracture healing as well as quantitative histomorphometry. We studied 14 patients. Baseline BMD, BTM, and TBS varied widely. On initial bone biopsies, 12 of 14 patients showed tetracycline labels, but mineralizing surface/bone surface was below published normal values in all but 2. Lumbar spine BMD increased significantly at month 24 (6.1% ± 4.3%, p < 0.05 versus baseline), whereas total hip BMD and TBS did not change significantly. Changes in BTM occurred as reported previously for patients without AFF treated with teriparatide after prior bisphosphonate treatment. At month 24, fractures were healed in 6 patients, showed partial healing in 3, were unchanged in 2, and showed nonunion in 1. In a patient with two fractures, the fracture that occurred before teriparatide treatment was reported as healed, but the fracture that occurred while on treatment showed only partial healing. Bisphosphonate‐treated patients who sustain AFF show heterogeneity of bone turnover. Treatment with teriparatide resulted in increases in BTM and lumbar spine BMD, as has been reported for patients without AFF. There was no significant effect of teriparatide on hip BMD, mineralizing surface to bone surface (MS/BS), or TBS and no consistent effect on fracture healing. In the context of a patient who has experienced an AFF after receiving bisphosphonate treatment, therapy with teriparatide for 24 months would be expected to increase BMD and BTM (and probably reduce the risk of fractures resulting from osteoporosis) but should not be relied on to aid in healing of the AFF. © 2017 American Society for Bone and Mineral Research.